The Educational Effects of Rural Adolescents' Social Networks - Kusum Singh; Sandra Dika (Journal of Research in Rural Education, 2003)
This study e xplored the social networks and sources ofsocial supportfor rural high-school ado lescen ts and hall' these are related 10 educational and psychological outcomes. IJe examined quality . frequency. and nature ofsocial relationships ofhigh school students to understand how size. density. heterogeneity. compositional quality ofsocial network, and frequency ofinteraction affected educational aspiration and academic engagement ofrural youth. Results showed that academic support and emotional support provided by network members exp lained a significant. though moderate, amount of variance in educational outcomes.